Scientific-Pedagogical Activity of Volodymyr Otrokovskyi: Historic-Literary Aspect - Vitalii Matsko (Pedagogical Discourse, 2014)
In the article special attention is paid to the worldview function of the researcher of ancient Ukrainian literature, poet, teacher-philologist V.M. Otrokovskyi, who came out of the scientific philological seminar of the academician V.M. Peretts. The fate gave to Otrokovskyi only 25 years of life, but even during this short period of his persistent intellectual work he was able to leave noticeable mark on the Earth, to bring in strong contribution into the development of the domestic culture and education. Seriously he took great interest in science in 1911. During seven years he wrote ponderable researches «Narrative about the Merchant Basarg and its Literary Sources» (manuscript), «Motives of the Riddles of Wise Questions in Tales» (manuscript), «Tarasii Zemka – South Russian Literary Figure of the XVII Century» (1915), which consists of 3000 pages of printed text, “Motives of Heretics’ Persecution in Polemics of Zavoriye Aged Men and Josephites», «Commentaries to the Article of Aleksei Putintsev» (1880-1937), «The Most Ancient Russian Domostroy» (Voronezh, 1916), «Review to the Book of Fedor Riazanovsky», «Demonology in Ancient Russian Literature» (M., 1915), «Horatio and Trediakovsky» (unfinished) and others. All researches of Otrokovskyi were of great success in scientific circles, in its time they were warmly characterized by reputable Russian philologists, academicians A.Sobolevsky, V.Peretts, A.Shakhmatov, N.Nikolsky, V.Maikov.